Factors That Affect Audit Delay Through KAP Reputation as a Moderating Variable - Rafif Nathania Shadiq; Achmad Badjuri (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study investigates whether the characteristics of a company—specifically its size, profitability, and solvency—contribute to delays in the audit process, and explores if the prestige of the audit firm can influence this relationship. The research focuses on manufacturing companies listed on the Indonesia Stock Exchange (IDX) between 2022 and 2024, drawing on 150 financial reports collected over three years. Using a combination of regression analysis and moderation testing, the study finds that neither company size, profitability, nor solvency has a measurable effect on the timing of audit completion. Interestingly, the reputation of the auditing firm appears to buffer the impact of profitability on audit delays, but it does not alter the effects associated with company size or solvency. These findings suggest that other factors beyond basic financial metrics and firm stature may play a more decisive role in determining audit timelines.